2020
DOI: 10.1042/bcj20190342
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of Fast Endophilin-Mediated Endocytosis

Abstract: Endocytosis mediates the cellular uptake of micronutrients and cell surface proteins. Clathrin-mediated endocytosis (CME) is the housekeeping pathway in resting cells but additional Clathrin-independent endocytic (CIE) routes, including Fast Endophilin-Mediated Endocytosis (FEME), internalize specific cargoes and support diverse cellular functions. FEME is part of the Dynamin-dependent subgroup of CIE pathways. Here, we review our current understanding of the molecular mechanism of FEME. Key steps are: (i) pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
108
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(111 citation statements)
references
References 147 publications
(308 reference statements)
2
108
0
1
Order By: Relevance
“…While EIPA predominantly inhibits macropinocytosis, it is also capable of inhibiting fast endophilin mediated endocytosis (Boucrot et al, 2015). Fast endophilin mediated endocytosis strictly requires growth factors present in serum (Boucrot et al, 2015; Casamento and Boucrot, 2020) therefore to minimise any potential contribution of this alternate endocytic pathway, all experiments were performed in serum free media following a minimum of 1 hour serum starvation. Specific inhibition of macropinocytosis by addition of EIPA in serum free media lead to robust inhibition of Lp(a) uptake (Figure 1C,D) confirming macropinocytosis is an important endocytic mechanism for Lp(a) internalisation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While EIPA predominantly inhibits macropinocytosis, it is also capable of inhibiting fast endophilin mediated endocytosis (Boucrot et al, 2015). Fast endophilin mediated endocytosis strictly requires growth factors present in serum (Boucrot et al, 2015; Casamento and Boucrot, 2020) therefore to minimise any potential contribution of this alternate endocytic pathway, all experiments were performed in serum free media following a minimum of 1 hour serum starvation. Specific inhibition of macropinocytosis by addition of EIPA in serum free media lead to robust inhibition of Lp(a) uptake (Figure 1C,D) confirming macropinocytosis is an important endocytic mechanism for Lp(a) internalisation.…”
Section: Resultsmentioning
confidence: 99%
“…Clathrin-dependent and fast endophilin mediated endocytosis represent mechanisms of receptor-mediated endocytosis. In both cases, cargo/ligand binding to the receptor leads to the assembly of adaptor and coat proteins around the forming endosome which promote receptor and cargo internalisation (Boucrot et al, 2015; Casamento and Boucrot, 2020; Haucke, 2006; Traub and Bonifacino, 2013). In contrast, macropinocytosis is a calcium-dependent endocytic pathway where cargo is internalised via membrane remodelling events as opposed to receptor-mediated initiation of endocytosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endophilin plays a central role in FEME by driving cargo recruitment, membrane curvature generation, and membrane scission (14,15). It has been suggested that molecular interactions occur between the endophilin SH3 domain and the third intracellular loop (TIL) of several GPCR family members during their internalization through the FEME pathway (10,16,17). Still, it has remained unclear how membrane remodeling by endophilin is functionally coupled with protein-protein interactions mediated by the SH3 domain.…”
Section: Introductionmentioning
confidence: 99%
“…Endophilin plays a central role in FEME by driving cargo recruitment, membrane curvature generation, and membrane scission ( 14 , 15 ). It has been suggested that molecular interactions occur between the endophilin SH3 domain and the third intracellular loop (TIL) of several GPCR family members during their internalization through the FEME pathway ( 10 , 16 , 17 ). Still, it has remained unclear how membrane remodeling by endophilin is functionally coupled with protein–protein interactions mediated by the SH3 domain.…”
mentioning
confidence: 99%